Manifesto and proclamation : To the members of the Congress, the members of the general assemblies or conventions of the several colonies, plantations, and provinces of New Hampshire, Massachusetts Bay, Rhode Island, Connecticut, New York, New Jersey, Pennsylvania, the three lower counties of Delaware, Maryland, Virginia, North Carolina, South Carolina, and Georgia, and all others, free inhabitants of the said colonies, of every rank and denomination - Americanus, active 1778; Carlisle, Frederick Howard, Earl of, 1748-1825; Clinton, Henry, Sir, 1738?-1795; Auckland, William Eden, Baron, 1744-1814 (LLMC-digital (Series), 1778)
Offering terms for a general peace and pardon, with a reply signed Americanus.